Peran Sosial dan Keagamaan Manggalīa di Vihara Surya Putra Dusun Ngadisari : Studi Kepemimpinan Spiritual Buddhis Pedesaan - Danu Aryanto; Hesti Sadtyadi (Jurnal Budi Pekerti Agama Buddha, 2025)
This study examines the social and religious roles of a Manggalīa within the Buddhist community, with a case study in Dusun Ngadisari, Tempuran Village, Kaloran District, Temanggung Regency, Central Java. The Manggalīa is a local religious figure who serves as both an elder and leader of the community in various religious rituals such as weddings, funerals, patidāna, and traditional ceremonies including gendurenan, nyadran kubur, and village selametan. In Buddhist communities without a pandita, the Manggalīa plays a central role as a spiritual guide and preserver of local traditions. This research employs a qualitative descriptive approach using observation, in-depth interviews, and documentation methods. The selection of a Manggalīa is conducted through communal deliberation, based on spiritual and ritual competence, particularly in the aspects of sīla, samādhi, and paññā. The findings show that the Manggalīa in Dusun Ngadisari fulfills his role with great dedication, both in guiding the community's spiritual life and participating in social matters such as conflict mediation, community empowerment, and maintaining social harmony among villagers.